PREDIKSI FINANSIAL DISTRESS DENGAN METODE ALTMAN Z-SCORE, ZMIJEWSKI, DAN GROVER PADA PERUSAHAAN SAWIT TERINDEKS SAHAM SYARIAH PERIODE 2020-2022 - Abd Hadi; Dahruji Dahruji; Joni Joni (LP2M Universitas Ibrahimy, 2024)
The primary aim of this research is to analyze the financial challenges encountered by sharia-compliant palm oil companies, along with assessing the variances in financial distress prognostications among the Altman Z-Score, Zmijewski, and Grover methodologies. Employing secondary data, this study adopts a descriptive quantitative approach. Data collection spans three years (2020–2022) utilizing a documentation strategy. Through purposive sampling, six companies are selected for analysis. Financial trouble predictions are conducted utilizing Altman Z-Score, Zmijewski, Grover, and One Way Anova methods prior to hypothesis testing. The study reveals disparate outcomes among the Grover, Zmijewski, and Altman Z-Score methodologies. Notably, the Zmijewski approach exhibits the highest accuracy rate of 83% among the predictive models for financial distress.